The Influence of Social Media Usage Behavior on Intention to Leave - Arsanti, Tutuk Ari; Putri, Christy Elindia (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This research aims to examine the impact of various purposes for social media usage—specifically, information use (X1), hedonic use (X2), and social use (X3)—on the intention to leave (Y) among university lecturers in Indonesia. A quantitative methodology is employed, collecting data through a questionnaire distributed to 100 regional university lecturers. The analysis is conducted using multiple linear regression with SPSS version 26 software. The findings reveal that: 1) information use does not significantly influence the intention to leave; 2) hedonic use also shows no significant effect on the intention to leave; and 3) social use has no substantial impact on the intention to leave. This may be because the academic profession offers a greater opportunity for social interaction, which can alleviate work-related stress and reduce the desire for entertainment outside of work.